RECONCEPTUALIZING ETHNOMATHEMATICS-BASED ASSESSMENT: TEACHERS’ BELIEFS AND IMPLICATIONS FOR MATHEMATICS EDUCATION - Dewi Purnama Sari; Jailani Jailani; Sri Andayani (Universitas Labuhanbatu, 2026)
Objective – This study aims to examine in depth how teachers’ beliefs influence the conceptualization and practice of ethnomathematics-based assessment in mathematics education.Methodology – This study employs a descriptive qualitative approach, involving 10 junior high school mathematics teachers in Deli Serdang. Data collection was conducted through semi-structured interviews, and data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing.Findings – The results indicate that ethnomathematics-based assessment is understood not merely as a technical innovation in evaluation but as a pedagogical and epistemological process that connects mathematics, culture, and students' learning experiences. Teachers view mathematics as a universal science that can be interpreted within local cultural contexts; consequently, assessments aligned with students' socio-cultural realities are deemed more meaningful. This study also found that ethnomathematics-based assessment is a process of cultural mathematization that involves identifying cultural practices, transforming mathematical concepts, and translating them into contextual assessment activities. Furthermore, teachers' beliefs play a crucial role in the implementation of assessment, although a gap persists between teachers' positive beliefs and classroom assessment practices due to limited systemic support.Contribution – This study elucidates the process of cultural mathematization in assessment design and identifies the gap between beliefs and practices as a basis for developing more contextually relevant training and educational policies